Socio-demographic characteristics of employees and flexible work arrangements: Evidence from Serbia - Dimitrije Gašić; Nemanja Berber; Maja Strugar Jelača; Tibor Zsigmond (Anali Ekonomskog fakulteta u Subotici, 2025)
The turbulent environment that influences the contemporary business has caused a reconfiguration of operations, where organizations have developed flexible work arrangements that involve the modification of traditional work. The goal of applying various forms of flexible work arrangements is to attract and retain talent, develop employee skills and capabilities, and become more innovative in terms of job organization. The aim of the research is to investigate differences in the use of flexible work arrangement according to socio-demographic characteristics of employees in the Republic of Serbia. The research was conducted on a sample of 582 employees, using the independent sample T-test and univariate analysis of variance (ANOVA) by using the IBM SPSS software for data processing. The research results indicated that there are statistically significant differences between employees who use flexible work arrangements according to gender, age, and level of education, and accordingly, the research hypothesis was confirmed. The scientific contribution is focused on a key segment related to the lack of scientific research on this topic in the Republic of Serbia and beyond. The results represent significant propositions for future research in this field and provide a basis for amending labor laws.